Benefit and sacrifice factors affecting customer satisfaction toward adoption of internet banking in Iraqi Kurdistan region - Majeed, Ashty Rasull (2020)
As an information-intensive industry, the banking industry has been significantly influenced by information technology, particularly the Internet explosion and Internet banking service. Internet banking experience varies across different situations in various countries, thus generating dissimilar banking customers' attitudes and behaviours. While some countries have successfully installed this service in their banking sector and persuaded their customers to adopt it, some have not. For instance, the Iraqi Kurdistan Region (IKR) isstill experiencing difficulties related to Internet banking adoption. IKR has a population of 5.2 million, where a relatively large proportion is urban residents living in places where there are sufficient bank branches. IKR banks had been genuinely involved in IT integration in the 20th century. However, despite the appropriate potential IKR for adopting Internet banking, a large proportion of IKR bank patrons remain reluctant to replace face-to-face banking with this type of digital service. The reasons behind this reluctance and disinterest of bank customers in IKR are still unclear because of the scarcity of research on this issue. Thus, this research focuses on Internet banking adoption in IKR and sought to investigate the effect of benefit factors (perceived usefulness, perceived ease of use, perceived systemquality) and sacrifice factors (perceived cost and perceived risk) on behavioural intention to use and, in turn, actual use of Internet banking through the mediating role of customer satisfaction in the Iraqi Kurdistan banking sector. In order to achieve this aim, a model inspired by several theories and models, such as TRA, TAM, ISS, etc., was conceptualized. In this research study, a quantitative approach was adopted, and a self-administered questionnaire was used as the research instrument. Data were collected from 412 respondents, and based on the research objectives, they were analysed using descriptive and inferential analysis methods. Structural Equations Modelling (SEM) was applied as a suitable inferential ii analytical method to answer the research questions. The results generated revealed the significant role of benefit factors (perceived usefulness, perceived ease of use, perceived system quality) and sacrifice factors (perceived cost and perceived risk) on behavioural intention to use Internet banking through the mediating role of customer satisfaction, either directly or indirectly. Indeed, the findings demonstrated the pivotalrole of customer satisfaction in the adoption of Internet banking.